Emily Brontë’s Wuthering Heights in EFL Classroom: Writing Skills Focus - Akter Mukta, Rukaiya; Kabir, Md. Shahjahan; Yeasmin, Farhana (Language, Technology, and Social Media, 2025)
Integrating literature into language learning can prove to be a highly effective tool in an English as a Foreign Language (EFL) classroom. This is because a literary text encompasses various features related to language and linguistics. The exploration and utilization of these features in a language classroom can significantly advance students’ language skills, as literature leaves a lasting impact on their minds. Literature serves the dual purpose of entertaining and educating learners. Emily Brontë’s Wuthering Heights is an excellent source of different sentence patterns, rhetorical devices, idiomatic expressions, anaphoric and cataphoric references, ellipses, etc. Delving into the teaching and learning of these aspects can effectively enhance students’ writing skills. Traditionally, literary texts are taught with a focus on thematic and philosophical aspects, often neglecting linguistic elements. This study addresses and deconstructs these overlooked linguistic aspects, examining the practicality of incorporating novels into the EFL classroom. The study specifically aims at unveiling the role of Emily Brontë’s novel, Wuthering Heights, in English language learning, with a focus on how the novel can be employed as a valuable tool to advance students’ writing skills. The findings of this article may pave the way for a reconsideration of EFL syllabi, advocating the inclusion of literary texts as potential resources for developing students’ writing proficiency.